Cardiac troponin-T in acute rheumatic fever - (:unkn) unknown (My University, 2001)
Objective: Acute rheumatic fever is still one of the leading causes of mortality and morbidity due to heart disease in developing countries. Carditis is the most important manifestation of the disease and there are still difficulties in diagnosis. Cardiac troponin-T measurement has been found to be valuable in recognition of cardiac injury in various disease states. We investigated the cardiac troponin-T levels in patients with acute rheumatic fever and searched for a difference between patients with and without carditis. Methods: The study group consisted of 21 patients; 12 were girls and 9 were boys. Their age ranged between 6-16.5 years (mean±SD=11.9±2.5 yrs). Seven patients had only arthritis; 10 patients had both carditis and arthritis; and 4 patients had chorea as clinical diagnosis. Echocardiographic examination showed aortic and mitral regurgitation in 7, mitral regurgitation in 8 and aortic regurgitation in one patient. Serum levels of creatin phosphokinase (CK) and MB (CK-MB) fraction and cardiac troponin-T were measured during the diagnosis before the initiation of treatment in all patients. None of the patients had clinically overt congestive heart failure. Results: It was observed that CK and CK-MB levels were increased in one patient with carditis and arthritis while cardiac troponin-T levels were below the measurable levels in all patients. Conclusion: We concluded that cardiac troponin-T measurement has no value in detecting the presence of carditis in rheumatic fever. This may result from absence of myocardial necrosis despite the presence of intense myocardial inflammation.
Keywords: Carditis; Echocardiography; Rheumatic fever; Troponin